Aminoglycoside-mimicking carbonized polymer dots for bacteremia treatment. Issue 32 (1st August 2022) - Chiou, Yi-Ru; Lin, Chin-Jung; Harroun, Scott G.; Chen, Yi-Ru; Chang, Lung; Wu, An-Tai; Chang, Fu-Chieh; Lin, Yang-Wei; Lin, Han-Jia; Anand, Anisha; Unnikrishnan, Binesh; Nain, Amit; et al.
Abstract : Aminoglycoside-mimicking carbonized polymer dots (CPDs) for bacteremia treatment by blocking the synthesis of bacterial proteins and disrupting bacterial membranes. Abstract : Bacteremia and associated bacterial sepsis are potentially fatal and occur when the host response to microbial invasion is impaired or compromised. This motivated us to develop carbonized polymer dots (CPDsMan/AA ) from a mixture of mannose (Man) and positively charged amino acids [AAs; lysine, arginine (Arg), or histidine] through a one-step mild pyrolysis procedure, which effectively inhibited drug-resistant bacterial strains isolated from septic patients. The as-prepared CPDsMan/AA showed broad-spectrum antibacterial activity, including multidrug-resistant bacteria, even in human plasma. The minimal inhibitory concentration of CPDsMan/Arg is ca. 1.0 μg mL −1, which is comparable to or lower than those of other tested antibiotics ( e.g., ampicillin, gentamicin, and vancomycin). In addition to directly disrupting bacterial membranes, the CPDsMan/Arg feature a structure similar to aminoglycoside antibiotics that could bind to 16S rRNA, thereby blocking bacterial protein synthesis . In vitro cytotoxic and hemolytic assays demonstrated the high biocompatibility of the CPDsMan/AA . In addition, in vivo studies on methicillin-resistant Staphylococcus aureus -infected mice treated with the CPDsMan/Arg showed a significant decrease in mortality—even better than that of antibiotics. Overall, the synthesis of the CPDsMan/AA is cost-efficient, straightforward, and effective for treating bacteremia. The polymeric features of the CPDsMan/Arg, including cationic charges and specific groups, can be recognized as a safe and broad-spectrum biocide to lessen our reliance on antibiotics to treat systemic bacterial infections in the future.